2016
DOI: 10.1111/jfd.12503
|View full text |Cite
|
Sign up to set email alerts
|

Combined antiparasitic and anti‐inflammatory effects of the natural polyphenol curcumin on turbot scuticociliatosis

Abstract: The histiophagous scuticociliate Philasterides dicentrarchi is the aetiological agent of scuticociliatosis, a parasitic disease of farmed turbot. Curcumin, a polyphenol from Curcuma longa (turmeric), is known to have antioxidant and anti-inflammatory properties. We investigated the in vitro effects of curcumin on the growth of P. dicentrarchi and on the production of pro-inflammatory cytokines in turbot leucocytes activated by parasite cysteine proteases. At 100 μm, curcumin had a cytotoxic effect and complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 85 publications
(174 reference statements)
1
5
0
Order By: Relevance
“…The complement system is considered important in defence against P. dicentrarchi [11,20], and although complement levels are lowered in the serum of infected turbot [12], it is not known whether leishmanolysins participate in the process. Our results agree with those obtained in previous studies, which reported high level of leishmanolysin expression in a P. dicentrarchi isolate (I1) obtained from turbot infections [43], and UR of several leishmanolysin genes in Miamiensis avidus fed a cell line [44], suggesting that these molecules play a role in cell degradation. Thus, although the role of each regulated leishmanolysin gene in the success of P. dicentrachi infection remains to be established, it appears that leishmanolysins are probably involved in ciliate virulence.…”
Section: Discussionsupporting
confidence: 93%
“…The complement system is considered important in defence against P. dicentrarchi [11,20], and although complement levels are lowered in the serum of infected turbot [12], it is not known whether leishmanolysins participate in the process. Our results agree with those obtained in previous studies, which reported high level of leishmanolysin expression in a P. dicentrarchi isolate (I1) obtained from turbot infections [43], and UR of several leishmanolysin genes in Miamiensis avidus fed a cell line [44], suggesting that these molecules play a role in cell degradation. Thus, although the role of each regulated leishmanolysin gene in the success of P. dicentrachi infection remains to be established, it appears that leishmanolysins are probably involved in ciliate virulence.…”
Section: Discussionsupporting
confidence: 93%
“…has been previously tested in fish feed as an immunostimulator and booster in the antioxidant status and protein content [ 37 , 38 ]. Although it has been employed against many protozoan and few trematode infections in humans over the years [ 39 ], it has been recently introduced in aquaculture as an experimental and efficient treatment of the ciliates Ichthyophthirius multifiliis infecting carp [ 40 ] and Philasterides dicentrarchi infecting turbot [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 as a key member of cytokines plays key roles in immune process, including acute phase response, hematopoiesis, energy sensor, and immune cell differentiation through modulating immune-signaling pathways (51, 52). Simultaneously, as a pro-inflammatory factor, up-regulation of IL-6 transcripts was detected in many fish defending against various pathogenic infections (5355). Furthermore, IL-6 was found to drive lymphocyte differentiation after stimulation of trout head-kidney cells (56), indicating that it might be involved in fish immune response.…”
Section: Discussionmentioning
confidence: 99%